Implementasi SAK EMKM (Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah) Pada Laporan Keuangan UMKM (Studi Kasus Pada UMKM XYZ Yogyakarta) - Tatik Tatik (STIE Mandala Jember, 2018)
The perpetrators of SMEs generally do not use the standards applicable in the preparation of financial statements. MSME financial statements often use cash basis taken from daily cash mutation sources. The Indonesian Institute of Accountants seeks to contribute to overcome the constraints of MSMEs in the preparation of financial statements by issuing the Financial Accounting Standards of Micro Small and Medium Enterprises (SAK EMKM) and effective from 1 January 2018. SAK EMKM is simple to be implemented easily by MSMEs. The Financial Statements according to SAK EMKM are prepared on the accrual basis. This study aims to implement SAK EMKM in the preparation of financial statements of SMEs XYZ Yogyakarta. This research uses qualitative approach with case study method. The data used are primary data sourced from direct observation, interview and documentation of transaction evidence. The results of the research are the financial statements of MSME XYZ in the form of the statements of financial position, income statement and notes on financial statements. Keywords: MSME, financial report, SAK-EMKM, accrual basis, qualitative